Essential evidence-based introductory bioterrorism content for practicing nurses. (January 2019) - Sharma, Manu; Dixon, Jane K.; Carter, Eileen J.; McCorkle, Ruth
Abstract: Bioterrorism content is too often absent from nursing education post-licensure. According to the Centers for Disease Control and Prevention (CDC), bioterrorism is defined as "the deliberate release of viruses, bacteria, or other germs (agents) used to cause illness or death in people, animals, or plants." The purpose of this scholarly work was to develop and pilot a curriculum on introductory bioterrorism concepts for practicing nurses. A literature search and a review of available resources elucidated pertinent content items on bioterrorism and its associated precautions for nurses. Next, two rounds of expert panel consisting of five members rated the identified content and provided comments to validate the curriculum's content. Based on the results, content items were expanded into a curriculum that was piloted as a four hour in person educational session and nurses in attendance were invited to participate in pre-test and post-test questions. They were also asked for their perceptions of the educational session's usefulness and influence on patient care in case of a bioterrorism event. All respondents strongly agreed that the information presented would be useful to them and would influence their patient care in a bioterrorism event. Further refinement, evaluation, and implementation of the developed curriculum are recommended. Highlights: Currently post-licensure nurses possess bioterrorism knowledge and education deficits. The robust methodology for content development provides a framework for future nursing preparedness education. A curriculum on introductory bioterrorism knowledge was developed for practicing nurses. The curriculum was piloted with nurses at an academic medical center. All respondents strongly agreed with the usefulness of information and influence on their patient care in a bioterrorism event.